1991
DOI: 10.1002/1097-0142(19910115)67:2<529::aid-cncr2820670235>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of tumor diameter in carcinoma of the head of the pancreas

Abstract: Two hundred twenty patients with a carcinoma in the head of the pancreas were divided into three tumor diameter groups: group 1, 0.5 to 4.4 cm (n = 72); group 2, 4.5 to 6.0 cm (n = 77); and group 3, 6.1 to 15.0 cm (n = 71). For these tumor diameter groups a six-fold eliminatory curability analysis was performed. Of the patients with liver metastases in group 1 the last patient had died at 10 months and in groups 2 and 3 no patients were alive at 18 months after the start of complaints. Patients with extrahepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…Tumour size was not predictive of vessel or margin invasion; our study group consisted mainly of patients with tumours less than 5 cm in diameter. Beyond this size a significant increase in vessel invasion has been reported [14]. Node involvement has been shown to be a prognostically significant factor [8,10].…”
Section: Discussionmentioning
confidence: 99%
“…Tumour size was not predictive of vessel or margin invasion; our study group consisted mainly of patients with tumours less than 5 cm in diameter. Beyond this size a significant increase in vessel invasion has been reported [14]. Node involvement has been shown to be a prognostically significant factor [8,10].…”
Section: Discussionmentioning
confidence: 99%
“…The tumors were classified into four groups by maximum diameter: <2 cm (7), 2-4 cm (47), 4-6 cm (25), and >6 cm (11). Tumor sites were the head of the pancreas (69) and the body or tail of the pancreas (21). Lymph vessel invasion was detected in 89 cases (98.9%).…”
Section: Histologic Type Tumor Size Location Lymph Vessel Infiltramentioning
confidence: 99%
“…Tumor stage remains the most important factor prognostically (Allema et al, 1995). However, tumors less than 4.5 cms in diameter show the largest survival rates (Nix et al, 1991). A large study of 616 resected adenocarcinomas of pancreas showed that negative tumor margins (complete resection), tumor size (less than 3 cm) and well to moderate tumor differentiation are important prognostic indicators .…”
Section: Discussionmentioning
confidence: 99%